Carbon composition, surface porosities and dielectric properties of coconut shell powder and coconut shell activated carbon composites - Seok, Yew Been; Siti Nurbazilah, Ab Jabal; Hoon, Wee Fwen (2016)
This paper investigates the potential of coconut shell powder (CSP) and coconut shell activated carbon (CSAC) with epoxy resin matrix composites to be used as absorbing materials over frequency of 1-8 GHz. Carbonaceous materials are preferable to be used as electromagnetic absorbent due to its excellent thermal conductivity. The CHNS Elemental Analysis is performed to evaluate the carbon composition (%) of the raw CSP and CSAC. From CHNS analysis, it was found that the carbon % of CSP and CSAC is 48.37% and 83.94% respectively. The surface porosities of CSP and CSAC were examined using scanning electron microscope (SEM) at an accelerating voltage of 15 kV. The porosity of CSP and CSAC is in the range of 2µm and 1µm respectively. The dielectric properties (complex permittivity) of the composites were determined by using high temperature dielectric probe in conjunction with Network Analyser. The dielectric constant for CSP and CSAC is 3.769 and 7.240 respectively while the dielectric loss factor for CSP and CSAC is 0.289 and 0.859 respectively.